Perbandingan Pengaruh Pemberian Ekstrak Daun Pepaya (Carica papaya L.) dan Kurkuma terhadap Kerusakan Struktur Histologis Ginjal Tikus Putih (Rattus norvegicus) yang Diinduksi Parasetamol Dosis Toksik - Alfian Noor Hakim Kusumawan; Endang Listyaningsih S; Bambang Widjokongko (Nexus Biomedika, 2014)
Background: Papaya (Carica papaya L.) is an interesting plant because its leaves contain chlorophyll total, chlorophyll a and chlorophyll b those are higher than the chlorophyll in the leaves of other plants. In addition, this plant also contains antioxidant components such as vitamin C, beta carotene, and iron (Fe). This study aims to compare the renoprotection power between papayas leaves extract and curcuma. Methods: This study was a laboratory experimental research. The samples were twenty four male Wistar rats those were 8-12 weeks old and 160-250 grams of body weight. Samples were divided into 6 groups randomly, each group consisted of 4 rats. The KK group was not given any treatments. The KP1 group was induced by paracetamol but it was not given any renoprotector treatments. The KP2 group was induced by paracetamol and given curcuma. The KP3, KP4, and KP5 groups were induced by paracetamol and given papaya's leaves extract at dose of 150 mg, 300 mg, and 600 mg per kg body weight respectively. Renal histological structure were assessed by counting the cell nucleus that was pyknosis, karyorrhexis, and karyolysis. Data were analyzed by One-Way ANOVA test, then followed by Least Significance Difference (LSD) test (?=0.05). Results: One-Way ANOVA test showed that p value was 0.000 (p <0.05). The results of LSD test showed the significant differences in the pair of groups: KK-KP1, KK-KP2, KK-KP3, KK-KP4, KK-KP5, KP1-KP2, KP1-KP3, KP1-KP4, KP1-KP5, KP2-KP3, KP2-KP4, KP2-KP5, KP3-KP4, KP3-KP5, and there was no significant difference in a pair of group KP4-KP5. Conclusions: Papaya's leaves extract has a better renoprotection than curcuma and increasing dose of papaya's leaves extract can improve the renoprotection. Keywords: papayas leaves, curcuma, paracetamol, damaging kidney.